Pendugaan kerusakan Akibat Impak pada Buah Apel dengan Metode Elemen Hingga - Yuwana Yuwana (agriTECH, 2003)
Damage caused by impact in apple was predicted using finite element method Apple model was axi-•ymetric three dimensions consisted 779-1 tetrahylrical elemeitts with 1612 nodes representing an apple having 2.5 AlPa Yon; modulus, 0.145 Poisson ratio. 134.5 g mass and 164,4 cm . Impact was simulated by employing an acceleration of 135 g (g = 9,81m/s1) on the model. During simulation, damage was supposed to occur when the stress suffered by cell was greater than its strength. The strength of cell was adopted from the previous study which was 0.44 Zone q" damage resulted by impact was compared to the damage of the real apple caused by impact with the same energy level. The result of the simulation indicated that- the zone of damage in the apple matched to the damage of the real apple. This finding suggested that the finite element method could be employed to accurately predict the damage mechanism caused by impact on apple.